The perfect son - North, Lauren (Berkley, 2019)
"A disturbing and shocking debut novel of psychological suspense about a recently widowed mother, her young son, and the lengths she'll go to in order to keep him safe. When Tess Clarke wakes up in the hospital the day after her son Jamie's eighth birthday, she's sure of these things: She's been stabbed, her son is missing, her brother-in-law and her grief counselor are involved. But no one is listening to her. After her husband, Mark, died suddenly in a terrible accident a few months earlier, the only thing keeping Tess together is Jamie. As they struggle to make sense of their new life without Mark, they find joy in brief moments of normalcy like walking to school and watching television together. Life is hard without Mark, but Tess has Jamie, and that's what matters. But there in the hospital, confused and surrounded by people who won't listen, Tess's world falls apart. To save her son, she must piece together what happened between Mark's death and Jamie's birthday, but the truth might just be too much for her to bear"--